Effectiveness of home-based walking exercise for patients with peripheral artery disease and intermittent claudication: a systematic review and meta-analysis - Zheng Xu; Jing Chuo; Xiaoqin Zhao (BMJ Open)
Objective This study aimed to assess the effect of home-based exercise interventions on walking performance in patients with peripheral artery disease (PAD) and intermittent claudication (IC).Design Systematic review and meta-analysis.Data sources We searched the Medline, Web of Science, Embase, Scopus and Cochrane Library databases to identify randomised controlled trials of patients with PAD and IC published in English up to August 2024.Eligibility criteria Randomised controlled trials of patients who participated in home-based exercise interventions and were assessed for walking performance were eligible for inclusion. Studies without available data were excluded.Data extraction and synthesis We analysed the pooled effect size on walking performance based on the standardised mean differences between groups. A leave-one-out sensitivity analysis was performed to ensure the robustness of the findings.Results A total of eight studies were included in the meta-analysis. The duration of interventions in the included studies ranged from 6 to 52 weeks. In the pooled analysis, compared with control groups, the home-based exercise intervention groups showed improved pain-free walking distance (standardised mean difference 0.67, 95% CI 0.20 to 1.15), and maximal walking distance (0.47, 0.05 to 0.89). The overall heterogeneity score of pain-free walking distance was I2=83% (p<0.001), and for maximal walking distance, I2=78% (p<0.001).Conclusions Home-based exercise interventions for patients with PAD and IC were beneficial in improving pain-free walking distance and maximal walking distance. Future studies should consider multiple factors that may affect the effectiveness of home training and intervention compliance.Trial registration number PROSPERO, CRD42024499020.